Improvement of Student Learning Outcomes Through The Implementation Of The Problem Based Learning Model For Class IV Elementary School - Ita Laila Puji Rahmawati (Universitas Sebelas Maret, 2020)
This research is a classroom action research (PTK) which consists of two cycles. This PTK has two cycles in one cycle, there are four stages, namely planning, implementing, observing and reflecting. The research subjects were students of grade IV A SDN Pedurungan Lor 01 Semarang, Central Java with a total of 31 students. Data collection techniques using test and non-test techniques. The assessment instrument uses item items and observations of the scoring rubric. The results showed that the application of the Problem Based Learning learning model can improve student learning outcomes in Theme 4 Various Classes IV A SDN Pedurungan Lor 01 Semarang, this is evidenced by the learning outcomes in cycle I, namely 14 students out of 31 students or 45%, while students who completed as many as 17 students from 31 students or 55%. In cycle II, in the initial conditions according to the background of the research, there were 22 students out of 31 students or 71% who had not yet completed it. In cycle II, there were 7 students out of 31 students or 23% who had not completed, while 24 students out of 31 students or 77% who had completed it. This means that student learning outcomes increase from cycle I to cycle II. The conclusion of this study is that using the Problem Based Leraning learning model can improve student learning outcomes in Theme 4 Various Occupations of class IV A SDN Pedurungan Lor 01 Semarang.